INCORPORATING REAL-TIME DATA IN ONE WAY ROAD TO VALUE ROAD CAPACITY (CASE STUDY: AHMAD YANI AND TRUNOJOYO ROAD JEMBER) - Abriyawan, Muhammad Firmansyah; Kriswardhana, Willy; Suyoso, Hernu (Jurnal Ilmiah Teknik Sipil; Vol 25 No 2 (2021): Jurnal Ilmiah Teknik Sipil, Vol. 25 No. 2, Juli 2021DO - 10.24843/JITS.2021.v25.i02.p02, 2022)
Ahmad Yani and Trunojoyo are urban roads located in Jember City, East Java. There is a fundamental correlation in traffic between flow, speed, and density. To find out the correlation model of the three parameters, research with Greenshield, Greenberg, and Underwood models will be carried out which produce a capacity value. Once the capacity values of the three models have been calculated , then the capacity that is most appropriate to the MKJI 1997 capacity values is searched. This research was conducted on active working days (weekdays) conducted from 06.00 – 21.00 WIB. Based on the results of this study, the capacity value for the Ahmad Yani Street section from the Greenshield model is 3486,90 veh /hour, Greenberg is 14134 veh /hour, and Underwood is 4034 veh/hour. Meanwhile, f or the Trunojoyo Street section capacity value obtained from the Greenshield model is 3275,80 veh/hour, Greenberg is 12513,45 veh/hour, and Underwood is 3852,33 veh/hour. The capacity values based on the IHCM 1997 for Ahmad Yani Street is 3960 veh/hour and Trunojoyo is 4079 veh/hour. Based on the results of this study , the appropriate model for the Ahmad Yani Road section is the Underwood model and Trunojoyo Road is the Greenshield model.